Development of a Sustainable Information System Using Structured Routing and Livewire Methods in Educational Institutions in Jakarta - Fitrianto, Adi (Brilliance: Research of Artificial Intelligence, 2024)
This research aims to develop a data management application for instructors and training programs at MNC Academy. The underlying issue for developing this application is the lack of an efficient and practical data recording system and insufficient accessibility to important information about instructors and training. Instructor and training data are often complex and continually evolving, making manual management or using office software inefficient and time-consuming. Additionally, digital data recording of instructors and training is needed for the promotional website of MNC Academy, ensuring organized and timely access to relevant information for the public. The application is developed using PHP programming language with the Laravel framework as its base. The application also employs structured routing and Livewire technology to build mini components that support the system’s functionality more effectively. Structured routing is an approach to clearly and systematically organize routes, enabling more systematic management of URL links and providing a structured way to handle navigation routes. Livewire in the Laravel framework is a technology that allows the creation of interactive user interface components without the need to write separate JavaScript code. Using Livewire helps simplify the development of dynamic components by reducing technical complexity. With the implementation of this data management application, it is expected that the data of instructors and training programs at MNC Academy can be managed more systematically, enabling neat record-keeping and providing easier access for those needing this information.